The Analysis of The Decision No. 1706/Pdt.G/2020/PA.Mdn. Based on The Decision No. 93/PUU-X/2012 - Siregar, Muhaimin Nur; Siregar, Fatahuddin Aziz (Jurnal El-Thawalib, 2023)
This research discusses regarding the sharia economic dispute resolution based on akad which usually occures, with analyzed of the Medan Religious Court Decision No. 1706/Pdt.G/2020/PA.Mdn. according the Constitutional Court Decision No. 93/PUU-X/2012 regarding sharia economic dispute resolution based on akad. The type of this research is library research and in the form of normative legal research. The research approach uses statute approach and case approach with theoretical review by pure theory of law and positivism theory of law. The primary legal materials consist of UUD 1945, KUHPerdata, Law No. 21 of 2008 regarding the Sharia Banking, Law No. 3 of 2006 regarding Religious Courts, Law No. 30 of 1999 regarding Arbitration and Alternative Dispute Resolution, Law No. 3 of 2004 regarding the Constitutional Court, Medan Religious Court Decision No. 1706/Pdt.G/2020/PA.Mdn. and Constitutional Court Decision No. 93/PUU-X/2012. The secondary legal materials are books, thesis, and law journals according to the research problems. The colecting datas technique is documentation and the analysis technique uses desciptive analysis. The result of this reseacrh shows that the consideration of the Medan Religious Court Judges’ on the decision No. 1706/Pdt.G/2020/PA.Mdn. who declares that It was not authorized to try the lawsuit based on the explanation of Article 3 of Law No. 3 of 1999 which principally states that the court  is not authorized to try between parties who have been bound in an Arbitration akad and the Constitutional Court Decision No. 93/PUU-X/2012 does not make it has no legal force. Because the two legal standing is separated. Then, by reviewing of the Constitutional Court Decision No. 93/PUU-X/2012 toward the Medan Religious Court Decision No. 1706/Pdt.G/2020/PA.Mdn. regarding the sharia economic dispute resolution based on akad is contradict with law according to the pure theory of law and positivism theory of law. Because the explanation of Article 55 paragraph (2) of Law No. 21 of 2008 that stated sharia economic dispute resolution through arbitration contradict  with  UUD 1945.Sharia Economic Dispute, Dispute Resolution, Akad